Effect of Winning Experience on Aggression Involving Dangerous Fighting Behavior in Anastatus disparis (Hymenoptera: Eupelmidae). Issue 3 (27th May 2020) - Liu, Peng-Cheng; Hao, De-Jun; Hu, Hao-Yuan; Wei, Jian-Rong; Wu, Fan; Shen, Jie; Xu, Shen-jia; Xie, Qi-Yue
Abstract: Aggressive behavior is widely observed in animal species for acquiring important resources and usually includes both dangerous and nondangerous fighting patterns. Only a few species show dangerous fighting patterns that are defined by fights ending with contestants being severely injured or killed. Prior experience, an important factor in many species, has been demonstrated to affect a contestant's subsequent fighting behavior. Few studies have focused on the effect of experience on aggression involving dangerous fighting patterns. Here, an egg parasitoid wasp, Anastatus disparis, which shows extreme and dangerous fighting behavior to acquire mating opportunities, was used as an experimental model. Our results showed that the fighting intensity of the winning males significantly decreased subsequent fighting behavior, which was inconsistent with general predictions. Transcriptomic analyses showed that many genes related to energy metabolism were downregulated in winners, and winners increased their fighting intensity after dietary supplementation. Our study suggested that fighting in A. disparis is a tremendous drain on energy. Thus, although males won at combat, significant reductions in available energy constrained the intensity of subsequent fights and influenced strategic decisions. In addition, winners might improve their fighting skills and abilities from previous contests, and their fighting intensity after dietary supplementation was significantly higher than that of males without any fighting experience. Generally, in A. disparis, although winners increased their fighting ability with previous experience, the available energy in winners was likely to be a crucial factor affecting the intensity and strategic decisions in subsequent fights.